رؤية الأميرة الهندية سكندر بيگم للوضع الاجتماعي والثقافي في مكة وجدة في القرن الثالث عشر الهجري: Indian Princess Sikandar Begum’s Observations about the Socio-cultural Conditions of Mecca and Jeddah in the Thirteenth Century AH - Alam صاحب عالم الأعظمي الندوي (الدراسات الإسلامية, 2021)
This paper aims to study the socio-cultural conditions of Mecca and Jeddah during the nineteenth century AD. It examines these conditions through the account of Princess Sikandar Begum, Nawab of Bhopal, who made a pilgrimage to Mecca in 1863-1864 AD and stayed there for about six months. In her book titled Tārīkh-i Safar-i Makkah, Begum recorded details of the events, customs, and traditions that she observed. The importance of this account lies in the fact that it is one of the first Urdu accounts, in which one finds details about the socio-cultural conditions of Mecca and Jeddah. Most of the accounts and memoirs that were written by Indian travellers during that period only paid attention to the religious and spiritual manifestations of life in Arab cities. Begum’s memoir, on the other hand, is the first of its kind to offer a clear description of the social and cultural life of Arabia in the 1860s, with little attention to her spirituality. Thus, Begum’s account comes very close to an anthropologist’s record.